Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.mechatronics.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-law-based metamodels for the sizing of mechatronic systems

Abstract: This paper presents a new metamodel form and associated construction procedure adapted to the sizing tasks of mechatronics systems. This method of meta-modeling uses scaling laws to extract compact forms of design models from local numerical simulations (FEM). Compared to traditional metamodels (polynomial response surfaces, kriging radial basis function) the scaling-law-based metamodels have the advantage of a light, compact form and good predictive accuracy over a wide range of the design variables (several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…This system-level design, distinct from component design, needs to represent in the mechatronic layer the key information of the specific domain layer with dedicated models [5][6][7]. Referred to as "estimation models" by Budinger et al [7], they enable the designer to readily take multiple design constraints into account.…”
Section: Using Models To Size An Architecturementioning
confidence: 99%
See 3 more Smart Citations
“…This system-level design, distinct from component design, needs to represent in the mechatronic layer the key information of the specific domain layer with dedicated models [5][6][7]. Referred to as "estimation models" by Budinger et al [7], they enable the designer to readily take multiple design constraints into account.…”
Section: Using Models To Size An Architecturementioning
confidence: 99%
“…This system-level design, distinct from component design, needs to represent in the mechatronic layer the key information of the specific domain layer with dedicated models [5][6][7]. Referred to as "estimation models" by Budinger et al [7], they enable the designer to readily take multiple design constraints into account. The models 2 Hierarchical design models (after Hehenberger et al [4]) 3 Future Challenges in Mechatronics directly and explicitly link a few primary characteristics, such as overall dimensions of components, to the secondary characteristics needed for the sizing [5] and optimization [1].…”
Section: Using Models To Size An Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…It supposes to generate a Design of Experiments (DoE) 1 on a particular case study for which the integration parameters are varied, and then fit a regression model on the obtained data. The problem of the regression models such as polynomial, Gaussian RBF or Kriging is their nonphysical basis which in some cases gives poor predictive capability outside the DoE used for their construction [17]. Nevertheless, a recent paper has shown that if a physical base is used for the regression, the fitting gives simple relations with acceptable predictive capability outside the DoE [17].…”
Section: Necessity Of Simple Algebraic Models In Preliminary Designmentioning
confidence: 99%